2007
DOI: 10.1162/jiec.2007.1149
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Construction and Demolition Waste in Norway

Abstract: Current waste generation from the construction and demolition industry (C&D industry) in Norway is about 1.25 million tonnes per year. This article presents a procedure for projection of future waste amounts by estimating the activity level in the C&D industry, determining specific waste generation factors related to this activity, and finally calculating projections on flows of waste materials leaving the stocks in use and moving into the waste management system. This is done through a simple model of stocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 12 publications
2
101
1
4
Order By: Relevance
“…and new construction 16%, while demolition is 8% of the total building and construction activity, renovation 40% and new construction 52% [5]. Waste generation per gross floor area (WGA) at demolition is reported as being twenty times more [5] or even fifty times more than new construction [4].…”
Section: Literature Review Canddwmentioning
confidence: 99%
“…and new construction 16%, while demolition is 8% of the total building and construction activity, renovation 40% and new construction 52% [5]. Waste generation per gross floor area (WGA) at demolition is reported as being twenty times more [5] or even fifty times more than new construction [4].…”
Section: Literature Review Canddwmentioning
confidence: 99%
“…Similarly, different development stages of an economy will have different implications to C & D waste generation. For example, Bergsdal, Bohne [54] reported that in Norway demolition was the smallest C & D activities, contributing only 8% in 1998 while construction and renovation contributed 52% and 40% respectively to waste generation. In China, owing to the urbanization, demolition is the major culprit for waste generation [17,55], while in Hong Kong relative balanced activities between demolition and new construction can be seen owing to the renewal of the decayed urban areas.…”
Section: Economic Profiles In Relation To C and D Waste Managementmentioning
confidence: 99%
“…A number of MFA studies are available related to construction and demolition waste for countries and regions such as China (Shi et al 2012 ;Huang et al 2013 ), Japan ), The Netherlands (Müller 2006 ), Norway (Bergsdal et al 2007 ), and Taiwan (Hsiao et al 2002 ); for cities such as Beijing (Hu, D. et al 2010 ;Hu, M. et al 2010 ); and for specifi c infrastructures such as highway traffi c system (Wen and Li 2010 ).…”
Section: Construction and Demolition Wastementioning
confidence: 99%